WEAKLY EXPRESSED PECULIARITIES OF SPECIFIC HEAT OF SUPERCONDUCTIVE MATERIALS AND THEIR RELATION TO PARAMAGNETIC EFFECT, DETECTED BY SFCO METHOD - Kurghinyan, B. K.; Gevorgyan, S. G.; Ohanyan, V. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2023)
In the present paper we show that a fine paramagnetic peculiarity discovered recently in superconductors, and another weakly expressed effect noticed just before the well-known specific-heat jump (detected half a century ago by Corak and Satterthwaite, but passed unnoticed so far) have the same physical origin. To explain these effects and indicate the reason of their common origin we used an advanced conception, which admits the existence of two types of Cooper pairs in superconductive (SC) materials – singlet and triplet. According to our understanding, they show radically different, non-traditional temperature behaviour appon cooling of SC material, disscused in details in the present paper.
Keywords: paramagnetic peculiarity; superconductors; specific-heat jump; Cooper pairs